The Rate of Juvenile Delinquency in Segati Village Langgam District Pelalawan Regency - Fhatia Khoiroh; Daeng Ayub; Dafetta Fitrilinda (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
This study aims to see how high the level of juvenile delinquency that occurs in Segati Village, Langgam District, Pelalawan Regency. This study uses quantitative methods with descriptive statistical data analysis techniques and inferential statistical analysis with a sample of 238 respondents. process the data in this study Microsoft Excel and SPSS version 28 were used. The results of this study were juvenile delinquency in Segati Village, Langgam District, Pelalawan Regency based on each indicator included in the high category. Especially on indicators of compliance which have a high category. Therefore, the conclusion obtained is that juvenile delinquency in Segati Village, Langgam District, Pelalawan Regency is high and affects compliance, self-control, and social interaction in adolescents.